Are IBD patients more likely to have a prior diagnosis of irritable bowel syndrome?: report of a case-control study in the General Practice Research Database - Card, Timothy R.; Siffledeen, Jesse; Fleming, Kate M. (SAGE, 2014)
Background: Inflammatory bowel disease (IBD) patients are sometimes first diagnosed with irritable bowel syndrome (IBS), which may be construed as a misdiagnosis.